Historical Perspectives on Resource Use in Food Systems - Jemison, John; Beal, Amanda (Maine Policy Review, 2011)
No one would deny that industrial agriculture and fishing have been highly productive—but at what cost? This article explores the historical development and contemporary impact of food production on the environment, availability of water and other resources, energy, food safety, and even our waistlines
Keywords: Maine; food ecology; sustainable agriculture